Ventilator-delivered nasal intermittent positive pressure ventilation versus nasal biphasic positive airway pressure following extubation in infants ≤1250 g birth weight: a randomized trial. (16th February 2022) - Okur, Nilufer; Buyuktiryaki, Mehmet; Sari, Fatma Nur; Dizdar, Evrim Alyamac; Oguz, Serife Suna
Abstract: Background and objective: To determine the effectiveness of ventilator-delivered nasal intermittent positive pressure ventilation and nasal biphasic positive airway pressure (n-BiPAP) after first extubation attempt in infants ≤1250-g birthweight. Methods: This randomized controlled study included mechanically ventilated preterm infants of ≤1250-g birthweight who were randomly assigned to ventilator-delivered NIPPV or n-BiPAP at first extubation within 2 weeks of age. The primary outcome (extubation failure within 96 h following extubation) and secondary outcomes were compared. Results: Extubation failure occurred in 22 of 74 infants in n-BiPAP group and 34 of 75 infants in NIPPV group (OR 0.51, 95% CI: 0.26–1.002; p = .05). Duration of invasive and noninvasive ventilation were found to be similar between groups. Also, there were no significant differences among groups for intraventricular hemorrhage, medically/surgically treated patent ductus arteriosus, necrotizing enterocolitis, BPD or death. Conclusion: Sustained extubation in infants ≤1250-g birthweight and <2 weeks age did not differ between ventilator-delivered NIPPV and n-BiPAP. Trial registration: Clinical Trials.gov under identifier NCT02842190.